2019
DOI: 10.1007/jhep07(2019)089
|View full text |Cite
|
Sign up to set email alerts
|

Time-delayed electrons from Higgs decays to right-handed neutrinos

Abstract: We consider the physics reach at the high luminosity LHC (HL-LHC) using the timing capability of a minimum ionizing particle (MIP) timing layer and the electromagnetic calorimeter in the CMS experiment for a simplified right-handed neutrino effective theory. In the simplified model, the lightest right-handed neutrinos are produced through higgs decay with mean decay lengths of order O(0.1 m − 100 m) and then subsequently decay into final states that include electrons. We consider the effect of several differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The proposal for a MIP timing detector (MTD) [74] for the phase II CMS upgrade, which will provide the timing information for MIPs (minimum ionizing particles), can provide additional information which is relevant for the lifetime reconstruction of LLPs. A few recent works have already studied aspects of the role that such a detector could play in LLP searches [95,118]. It has also been shown in Refs.…”
Section: Including Precise Timing Informationmentioning
confidence: 98%
See 1 more Smart Citation
“…The proposal for a MIP timing detector (MTD) [74] for the phase II CMS upgrade, which will provide the timing information for MIPs (minimum ionizing particles), can provide additional information which is relevant for the lifetime reconstruction of LLPs. A few recent works have already studied aspects of the role that such a detector could play in LLP searches [95,118]. It has also been shown in Refs.…”
Section: Including Precise Timing Informationmentioning
confidence: 98%
“…As an example, the authors of [95] followed one CMS [96] and one ATLAS [97] analysis to estimate the double differential inclusive jet cross-section and the inclusive prompt photon cross-section, respectively. They found that if the probability to measure an object with a given lifetime is modelled as a gaussian smear with a time resolution of 30 ps (the standard deviation of the gaussian distribution), the number of background events mis-measured to have a time-delay of more than 1 ns was negligible, as 1 ns lies more than 30 standard deviations away from the central value of the distribution.…”
Section: A Note On Backgroundsmentioning
confidence: 99%
“…Recently, some precision timing detectors are proposed to be installed at CMS [49], AT-LAS [50,51] and LHCb [52]. These timing detectors, which aim to reduce the pile-up rate at the high luminosity LHC (HL-LHC), can also be used in long-lived particle searches [53][54][55][56]. In this analysis, we focus on one of the timing detectors, the minimum ionizing particle (MIP) timing detector to be installed to the CMS detector (hereafter MTD CMS) [49], which has a ∼30 pico-second timing resolution.…”
Section: Timing Detectormentioning
confidence: 99%
“…The dominant SM backgrounds come from the multi trackless jets in the same-vertex (SV) hard collisions and in the pile-up (PU) events [53], as well as photons in SV hard collisions [54]. The SV background arises because of the finite timing resolution; the PU background is due to the fact that within one bunch crossing, two hard collisions occurring at two different times can lead to a time delay signal.…”
Section: Jhep05(2020)055mentioning
confidence: 99%
See 1 more Smart Citation